Choose Your Clue Cards Learning Model in Writing Creative Cerpen Students of Indonesian Education and Literature Education STKIP Singkawang - Fitri Fitri; Mardian Mardian; Zulfahita Zulfahita (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This research is motivated by the low ability of student in creative writing short story. The thing that base the problem is the difficulty of students in exploring and developing idea. The problem in this research is how the learning model choose your clue cards (CYCC) in creative writing short story of student majoring in Indonesian language and literature education at STKIP Singkawang. This research focuses on studying the factual conditions of CYCC in creative writing short story writing in the Indonesian language and literature education department at the time the research was conducted. This research uses research and development methods and design or Research and Development (R&D). The development of this learning device refers to the 4-D device development model by Thiagarajan, et al. However, in this study, researchers only took 3-D, namely the stages of defining, designing, and developing. Keywords: CYCC, creative writing Abstrak Penelitian ini dilatarbelakangi oleh rendahnya kemampuan mahasiswa dalam menulis kreatif cerpen. Hal yang mendasari masalah tersebut adalah sulitnya mahasiswa dalam menggali dan mengembangkan ide. Masalah dalam penelitian ini adalah bagaimanakah model pembelajaran choose your clue cards (CYCC) dalam menulis kreatif cerpen mahasiswa jurusan pendidikan bahasa dan sastra Indonesia di STKIP Singkawang. Penelitian ini memusatkan perhatian pada penelaahan kondisi faktual CYCC dalam menulis kreatif cerpen di jurusan pendidikan bahasa dan sastra Indonesia pada saat penelitian dilaksanakan. Penelitian ini menggunakan metode dan desain penelitian dan pengembangan atau Research and Develepment (R&D). Pengembangan perangkat pembelajaran ini mengacu pada model pengembangan perangkat oleh 4-D Thiagarajan, dkk., namun dalam penelitian ini, peneliti hanya menempuh 3-D, yaitu tahap pendefinisian (define), perancangan (design), dan tahap pengembangan (develop). Kata kunci: model CYCC, menulis kreatif